"Education is Political Now": Pre-service Teacher Socialization in Politically Charged Times. Issue 2 (4th March 2022) - McCardle, Todd; Schroeder, Stephanie; Korson, Stacey
Abstract: Teacher protests across the country have garnered widespread attention. This qualitative study explores the role of four pre-service teachers (PSTs) in these protests by questioning what leads PSTs to join teacher rallies and examining how they perceived the impact of their participation on their personal and professional lives. Data sources include two semi-structured interviews using photo elicitation techniques where participants discussed pictures they shared from the rally. Using a socialization lens, we found the PSTs were motivated to protest by macro- (2016 election), exo- (media coverage) and micro-systems (role models) socialization. While the protest had differing impacts on each participant, the display of unity by teachers was profound. However, the professional impacts were limited based on each participant's prior socialization into the profession. Due to the promising influence of teacher educators on PST activism, we recommend teacher education take a more powerful role in the socialization of PSTs toward educational activism.